Teachers’ Perspectives on Factors Affecting EFL Learners’ Course Learning Outcomes: A Case Study - Almalki, Mansoor S. (Advances in Social Sciences Research Journal, 2019)
This study analyses the EFL teachers’ perceptions towards the efficacy of Course Learning Outcomes (CLOs). Using a detailed questionnaire to collect the related data from 138 teachers, who teach Regular English for Academic Purposes (REAP) and Intensive English for Academic Purposes (IEAP), the research paper offers variables such as teaching material in the form of books, supplementary material such as the online resources, students’ interest, teachers’ training on targeting their teaching to achieve the related CLOs, and time constraints to measure their impact on the actual attainment of the CLOs. The study is important as the respondents of the questionnaire are teachers who teach either teach REAP that .expands over a period of four continuous semesters (two years) and IEAP that covers the same course in two semesters (one year). The study has been carried out in a way that the REAP and IEAP respondents of the questionnaire have been place in two separate groups, adding another dimension to the research in terms of evaluating how the time factor influences, either negatively or positively, the attainment of the students’ CLOs.